Extended state observer/proportion integration differentiation compound control based on dynamic modelling for an aerial inertially stabilized platform. (30th November 2017) - Zhou, Xiangyang; Zhu, Jun; Zhao, Beilei; Li, Jianping
This article presents an extended state observer/proportion integration differentiation compound control scheme based on dynamic modelling for a three-axis inertially stabilized platform applied for aerial remote sensing. To reveal the effects of dynamic couplings among different gimbals and the base on the system control performance, the dynamic modelling of the inertially stabilized platform system is developed. Then, an extended state observer /proportion integration differentiation composite controller is designed to improve the tracking precision and stability of the inertially stabilized platform, whose disturbance rejection ability is analysed by simulations. During simulation analysis, the LuGre friction model is introduced to represent the effects of main disturbance torques. To verify the method, the experiments are conducted. The results show that the extended state observer/proportion integration differentiation compound scheme has excellent capability in disturbance rejection, by which the stabilization accuracy of the inertially stabilized platform has improved significantly.